Key competences in physics teaching and learning : selected contributions from the International Conference GIREP EPEC 2015, Wroclaw Poland, 6-10 July 2015 /: selected contributions from the International Conference GIREP EPEC 2015, Wroclaw Poland, 6-10 July 2015. (2016) - Unknown
No abstract available